Microfluidic Preparation of Liposomes Using Ethyl Acetate/n-Hexane Solvents as an Alternative to Chloroform - Eunhye Yang; Hyunjong Yu; Jun-Young Park; Kyung-Min Park; Pahn-Shick Chang (Journal of Chemistry)
Although liposomes have been used as a nutrient delivery carrier in the pharmaceutical, cosmetic, and food industries, they still suffer from the critical issue caused by the use of halogenated solvents (e.g., chloroform), which may be harmful to humans. Nonhalogenated solvents have been screened as candidate substitutes for chloroform based on their physicochemical properties. However, none of the candidates examined to date could form stable inverted micelles when used alone. Here, to obtain physicochemical properties similar to chloroform, combined mixtures were prepared using various ratios of each candidate. Based on the results of random combination trials with numerous candidates, ethyl acetate: n-hexane = 4 : 1(v/v) was selected as the optimum ratio because it could form stable inverted micelles and a transparent liposome solution without phase separation. The ethyl acetate and n-hexane mixture are a potential substitute for chloroform, which may resolve concerns regarding the toxicity of residual halogenated solvents in lipid nanovesicles.